THE IMPORTANCE OF EDUCATIONAL TECHNOLOGIES IN DEVELOPING DISCOURSE COMPETENCE IN SECONDARY SCHOOL STUDENTS (BASED ON A2 LEVEL LEARNERS) - Eshonqulova Sarvinoz; Berdiyorova Xilola Baxtiyor qizi; Mohiraxon Ergasheva Madaminjon kizi (Ustozlar uchun, 2025)
This paper investigates the impact of educational technologies on the development of discourse competence among secondary school learners, particularly at the A2 level. Discourse competence refers to the ability to produce and understand coherent spoken or written texts within communicative contexts. With the integration of digital tools and platforms in education, learners today have access to immersive, interactive, and personalized language learning environments. Through qualitative analysis and synthesis of recent literature, this paper demonstrates how technology-enhanced language instruction supports learners’ acquisition of discourse structures, promotes meaningful communication, and fosters autonomous learning. The findings suggest that when effectively implemented, educational technologies serve as a catalyst for improving discourse competence and preparing learners for real-world communication.